Compilation of analysis of tribotechnically modified composite polymer materials and their physicochemical, tribotechnical properties used in mechanical engineering (Международный научный журнал «Инженер», 2026)
His scientific article provides a detailed description of the modern development trends of modified compositepolymer materials used in mechanical engineering and other industries, their creation, tribotechnicalproperties, structural structure and practical application. The article presents the results of laboratory tests ofpolymer-based composite materials modified with organomineral fillers, their physicomechanical andtribological properties. The use of composite materials is of particular importance for parts of machines andmechanisms operating under high friction and load conditions. Such materials reduce the coefficient of frictionon surfaces, are wear-resistant, reduce the generation of static electricity and extend their service life. Inparticular, their use in the fields of cotton processing, chemical industry, agricultural machinery and energysignificantly increases efficiency. The article also analyzes the possibilities of improving the tribotechnicalproperties of composite polymer materials through their physicochemical and mechanochemical modificationon a scientific basis. Based on various structural components and their ratios, optimal composite compositionswere developed, and the most suitable options were identified based on the results of experiments conductedin laboratory conditions. The composite polymer materials developed in this scientific work are consideredone of the promising areas for the mechanical engineering industry.